Treatment of COPD exacerbations - Anzueto, Antonio (Henry Stewart Talks, 2012)
Treatment of COPD based on the underlying conditions, The most important causes of COPD exacerbations: viral and bacterial infections, Use of antibiotics in COPD, Treatment of patients who develop respiratory failure
Reviewed at 2022/01/23